Improving Student Learning Outcomes in Islamic Education Learning Using the Learning Assignment and Recitation Method at SD Negeri 23 Bandar Baru - Rajulis; Salmiati (MANDAILING GLOBAL EDUKASIA, 2025)
This classroom action research aimed to enhance Islamic Religious Education learning outcomes among fourth-grade students at SDN 23 Bandar Baru by implementing a combined approach of assignment-based learning and the recitation method. The study was motivated by the observation that students demonstrated low engagement and unsatisfactory academic performance in the topic of hadas kecil (minor ritual impurity), a fundamental concept in Islamic practices. Employing a cyclical model of planning, action, observation, and reflection, the research was conducted over three cycles involving 17 students as subjects. Data were collected through observation, field notes, and formative tests administered at the end of each cycle. The findings revealed a progressive improvement in student achievement: the average test scores increased from 66.5 in the first cycle to 70.16 in the second, and reached 83.33 in the third. Furthermore, classical completeness rose significantly from 23% to 77%, and finally to 94%. The results indicate that the integration of assignments with the recitation method effectively fostered student motivation, participation, and comprehension. Notably, students became more responsible and engaged in the learning process, while teachers were better able to structure learning activities around active and reflective engagement. In conclusion, the use of this integrated approach proved to be a practical and impactful method to improve student learning outcomes and should be considered for broader application in religious education contexts, particularly when aiming to internalize abstract and practice-based religious concepts.